Increasing Winter Wheat Grain Yield by Replicating the Management Adopted in High-Yielding Commercial Fields in Kansas during 2021–2022 - L. Ryan; L. Haag; J. D. Holman; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
Large winter wheat (Triticum aestivum) yield gaps between actual yields from farmers and yield potential in the U.S. Great Plains indicate the need to improve recommendations of best management strategies to profitably bridge these gaps. Many studies have compared individual management factors pre-determined by the individual researcher, but we are not aware of studies comparing combination of practices that producers are currently using, which would be more relevant for real-world scenarios. Our objective was to determine the yield gains resulting from management intensification using the combination of practices currently adopted in commercial wheat fields. Four management intensities (i.e., low, average, high, and top) were derived from a survey of 656 commercial wheat fields, and replicated in trials conducted in six western Kansas locations (cultivated after a sorghum-fallow period) and six central Kansas locations (directly no-tilled following soybean) during the 2021–2022 growing season. Management intensities were tested factorially on two adapted varieties which differed between central and western sites. Grain yield in central Kansas ranged from 37.1 bu/a in the low management intensity to 47.3 bu/a in the top intensity, with increases in yield of 14%, 6%, and 5% from the low to average, average to high, and high to top management intensities, respectively. The variety WB4269 outyielded Zenda (44.6 and 41.3 bu/a) across central environments. In western Kansas, there was a significant management effect, where wheat yield increased from the low intensity to the high and top intensities (from 45.9 to 60.1–61.4 bu/a); though WB-Grainfield and KS Dallas varieties had similar yields. Using similar management practices as the high yielding producers in central and western Kansas increased yields from the low- or average-management intensities, while further increases in management intensification sometimes resulted in no yield increases. Variety selection played an important role to increase attained yields in central Kansas but was dependent on location in western Kansas.
Keywords: yield gap; intensive management; variety-specific management; on-farm survey